2014
DOI: 10.1039/c4cp03533j
|View full text |Cite
|
Sign up to set email alerts
|

Substrate-controlled band positions in CH3NH3PbI3perovskite films

Abstract: Using X-ray and ultraviolet photoelectron spectroscopy, the surface band positions of solution-processed CH3NH3PbI3 perovskite thin films deposited on an insulating substrate (Al2O3), various n-type (TiO2, ZrO2, ZnO, and F:SnO2 (FTO)) substrates, and various p-type (PEDOT:PSS, NiO, and Cu2O) substrates are studied. Many-body GW calculations of the valence band density of states, with spin-orbit interactions included, show a clear correspondence with our experimental spectra and are used to confirm our assignme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

29
185
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 184 publications
(222 citation statements)
references
References 45 publications
(67 reference statements)
29
185
1
Order By: Relevance
“…We observe that the Fermi levels for the 15, 35, and 120 nm thick perovskite films deposited on PEDOT:PSS (5.02, 5.05, and 5.15 eV, respectively) were strongly influenced by the WF of the PEDOT:PSS (measured at 5.00 eV), i.e., the Fermi level of the perovskite was “pulled” toward that of PEDOT:PSS 40, 41. This implies that the depletion width of the perovskites on PEDOT:PSS extended through the bulk of the film 42.…”
mentioning
confidence: 92%
“…We observe that the Fermi levels for the 15, 35, and 120 nm thick perovskite films deposited on PEDOT:PSS (5.02, 5.05, and 5.15 eV, respectively) were strongly influenced by the WF of the PEDOT:PSS (measured at 5.00 eV), i.e., the Fermi level of the perovskite was “pulled” toward that of PEDOT:PSS 40, 41. This implies that the depletion width of the perovskites on PEDOT:PSS extended through the bulk of the film 42.…”
mentioning
confidence: 92%
“…On ptype substrates, such as PEDOT:PSS, NiO and Cu 2 O, the Fermi level of MAPbI 3 shifts closer to mid-gap. 185 These examples show the importance of characterizing the absorbers on the charge transport layers they would be paired with and to report the substrate with the PES measurements. Sample degradation during photoemission spectroscopy measurements Evaluating the degree of degradation during the measurements when characterizing these soft materials has been demonstrated to be crucial for a robust and accurate analysis of the properties described above.…”
Section: Influence Of Substrate On Band Positionsmentioning
confidence: 99%
“…[23] The use of other contact materials of diverse electronic character (either n-or p-type, and insulating) have revealed that the Fermi level within MAPbI 3 is strongly influenced by the substrate conductivity type. [24] In connection with the electronic interfacial properties, recent electrical measurements have shown that the potential drop concentrates near the TiO 2 /MAPbI 3 contact forming a sort of p-n junction. [25,26] But interfaces evolve during solar cell operation, presumably by the presence of moving ions, in such a way that the connection between photoemission spectroscopy findings and the reported V J − distortions needs of complementary analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Interfacial electronic properties as energy level alignment constitute a relevant piece of knowledge that can be addressed through photoemission spectroscopies. [23,24] From these works several recommendations for proper interface engineering are extracted. It is recognized that spiro-OMeTAD exhibits a non-optimum energy level alignment at interfaces with perovskite absorbers, while the TiO 2 conduction band is in relatively fair energy alignment.…”
Section: Introductionmentioning
confidence: 99%